Why are plant pathogens under-represented in eco-climatic niche modelling?. Issue 3 (3rd July 2019) - Ireland, Kylie B.; Kriticos, Darren J.
Abstract: Eco-climatic niche models are powerful tools for assessing the potential range of plant pests and pathogens, widely applied in comprehensive pest risk assessments globally. We conducted a bibliometric analysis comparing the number of CLIMEX models developed for plant pathogens and plant arthropod pests. We found that plant pathogens were statistically significantly under-represented, with fungal plant pathogens less than half as likely as plant insect pests to be the subject of a published CLIMEX niche model. We explore key factors that may account for this disparity, including inconsistent experimental paradigms and lack of cross-disciplinary (i.e., plant pathology and modelling) expertise.